Ammonium transporter 1 increases rice resistance to sheath blight by promoting nitrogen assimilation and ethylene signalling. Issue 6 (24th February 2022) - Wu, Xian Xin; Yuan, De Peng; Chen, Huan; Kumar, Vikranth; Kang, Seong Min; Jia, Baolei; Xuan, Yuan Hu
Summary: Sheath blight (ShB) significantly threatens rice yield production. However, the underlying mechanism of ShB defence in rice remains largely unknown. Here, we identified a highly ShB‐susceptible mutant Ds‐m which contained a mutation at the ammonium transporter 1;1 (AMT1;1) D 358 N. AMT1;1 D 358 N interacts with AMT1;1, AMT1;2 and AMT1;3 to inhibit the ammonium transport activity. The AMT1 RNAi was more susceptible and similar to the AMT1;1 D 358 N mutant; however, plants with higher NH4 + uptake activity were less susceptible to ShB. Glutamine synthetase 1;1 ( GS1;1 ) mutant gs1;1 and overexpressors ( GS1;1 OXs ) were more and less susceptible to ShB respectively. Furthermore, AMT1;1 overexpressor ( AMT1;1 OX ) /gs1;1 and gs1;1 exhibited a similar response to ShB, suggesting that ammonium assimilation rather than accumulation controls the ShB defence. Genetic and physiological assays further demonstrated that plants with higher amino acid or chlorophyll content promoted rice resistance to ShB. Interestingly, the expression of ethylene‐related genes was higher in AMT1;1 OX and lower in RNAi mutants than in wild‐type. Also, ethylene signalling positively regulated rice resistance to ShB and NH4 + uptake, suggesting that ethylene signalling acts downstream of AMT and also NH4 + uptake is under feedback control. Taken together, our data demonstrated that the AMT1 promotes rice resistance to ShB via the regulation of diverse metabolic and signalling pathways.